PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BIMA - Juniarty, Mira; Jaenab; Mawar Hidayati (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This research aims to determine the influence of work ability and work motivation on job satisfaction at the Bima Regency Public Works and Spatial Planning Service. The research instrument used in this research was a Likert scale questionnaire. The population used in this research were all employees at the Public Works and Spatial Planning Department of Bima Regency, totaling 167 respondents, consisting of 122 employees with civil servant status and 45 honorary staff so that the sample for this study was 122 employees with civil servant status at the Public Works Department. and Bima Regency Spatial Planning. The sampling technique was carried out using the purposive sampling method. The data in this research were collected by means of observation, interviews, questionnaires and literature study, then the data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests with SPSS version 26 assistance. The research results show thatwork ability and work motivation have a significant effect on job satisfaction at the Public Works and Spatial Planning Department of Bima Regency.